Governance and regulation of power pools and system operators : An international comparison - Barker, James, Jr (World Bank Technical Papers, 1997)
This paper compares and contrasts the governance and regulation of power pools in England and Wales, Victoria (Australia), Alberta (Canada), and Scandinavia (Norway and Sweden). Governance is the process by which decisions get made, implemented and enforced--it is internal to the pools. In contrast, regulation is how governments review and change the decisions of pools--it is external to the pools. The pools are organized markets for trading in electricity commodities and services. These "new style" power pools are created to maximize competition in generation, to compete on price, and to open to all market participants. Section I describes four basic models of power pool governance and the implementation issues associated with each model. Section II gives an overview of the similarities and differences among the four pools and how they affect governance. Section III examines how each pool has dealt with a number of basic governance decision. Section IV looks at how the pools monitor the markets that they have created. Section V describes different ways in which regulators and other government institutions control pools and how this control is exercised. Section VI presents some conclusions and observations